2015
DOI: 10.1093/alcalc/agv048
|View full text |Cite
|
Sign up to set email alerts
|

Beer Is Less Harmful for the Liver than Plain Ethanol: Studies in Male Mice Using a Binge-Drinking Model

Abstract: Our data suggest that beer is less harmful on the development of acute alcohol-induced liver damage than plain ethanol in male mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…This diet allows for alcohol consumption of clinical relevance and offers flexibility to adjust to special experimental or physiologic needs by allowing for various substitutions required for a particular experimental design, including changes in lipids, carbohydrates or other dietary constituents [35]. In contrast, alcohol administration in water is associated with insufficient consumption and heavy weight loss [22,36]. In our current study, we have found that rats of HF-EFr group consumed 10.0 g ethanol/kg BW/day per rat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This diet allows for alcohol consumption of clinical relevance and offers flexibility to adjust to special experimental or physiologic needs by allowing for various substitutions required for a particular experimental design, including changes in lipids, carbohydrates or other dietary constituents [35]. In contrast, alcohol administration in water is associated with insufficient consumption and heavy weight loss [22,36]. In our current study, we have found that rats of HF-EFr group consumed 10.0 g ethanol/kg BW/day per rat.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of alcohol drinking [55] including enhancing insulin sensitivity and adiponectin levels in postmenopausal women [56], and preventing the onset of NAFLD in ob / ob mice have been reported [22,57]. Consumption of HFD decreased adiponectin expression in rodents [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for these contradictory findings have not yet been fully understood; however, so far, in most of the studies participants were not stratified according to their consumption of fermented and distilled alcoholic drinks. Indeed, results of studies in patients suffering from liver cirrhosis consuming alcohol but also animal studies using high concentrations of alcohol (6.5 g EtOH/kg/bw) suggest that the kind of alcoholic drink might be critically affecting the progression of liver disease [10][11][12]. For instance, it has been shown that secondary plant compounds such as xanthohumol and isoα-acids found in hop or resveratrol found in grapes at least in experimental settings may beneficially affect the development of liver diseases of various etiologies including NAFLD [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, resveratrol, a polyphenolic compound notably presented in red wine, has been reported to prevent hepatic steatosis and endoplasmic reticulum stress induced by long‐term high‐fat diet . The hops in beer markedly attenuated acute alcohol‐induced liver steatosis . Er Guo Tou (EGT) is a very common and popular Chinese spirit, especially in the northeast and north of China.…”
Section: Introductionmentioning
confidence: 99%